Keberlanjutan Blue Economy Melalui Kontribusi Industri Ikan Tangkap Dan Budidaya Ikan Terhadap Pertumbuhan Ekonomi Provinsi Jawa Timur - Tri Lailatul Humairoh; Idfi Setyaningrum; Olivia Tanaya (Journal of Economic, Bussines and Accounting (COSTING), 2024)
Indonesia is a maritime country that has two-thirds of its ocean area larger than its land area and has 17,500 islands along 108,000 km of coastline. Indonesia's oceans provide a source of economic income that can support economic activities every year. The Blue Economy is aligned to increasing marine economic activities without destroying the ecosystem and preserving marine resources in a sustainable manner. The research carried out was to analyze the influence of caught fish and fish cultivation on economic growth in East Java. Researchers use multiple linear regression analysis with the Ordinary Least Square (OLS) method and secondary data types in the form of numerical numbers which will be processed using Statistical Tests in Eviews software. The time series data used comes from the official BPS (Central Statistics Agency) website for 5 years. The results of the research show that captured fish production and fish cultivation have a significant and significant impact on economic growth in East Java. Fish Catching and Fish Cultivation will have an even greater impact if the East Java Government increases new innovations such as implementing the Blue Economy on every coast where Fish Catching and Fish Cultivation occurs in East Java.